Crumbotti and rose petals in a ghost mountain valley: foraging, landscape, and their transformations in the upper Borbera Valley, NW Italy - Michele F. Fontefrancesco; Dauro M. Zocchi; Roberta Cevasco; Rebekka Dossche; Syed Abidullah; Andrea Pieroni (BMC, 2022)
Abstract Background The abandonment of mountain areas in Europe is a process that started during industrialisation and whose traces are still present nowadays. Initiatives aimed at stopping this decline and preserving the local biological and cultural diversities reflect the crucial issue of fostering sustainable rural development. This article contributes to the ongoing debate in assessing and preserving local ecological knowledge (LEK) in a highly marginalised mountain community in the Piedmontese Apennines to support local development. In so doing, it continues a larger project assessing how local botanical knowledge and landscapes evolve over time, in order to understand in more depth which factors affect how LEK is shaped, eroded, and re-created, and how this could be revitalised. Methods We compared information about the current gathering and use of local wild plants in the upper Borbera Valley (Carrega Ligure municipality, NW Italy), elicited via 34 in-depth open and semi-structured interviews, with the findings of a field study conducted in the same location, most likely carried out at the end of the 1970s and published in 1981. Results There were remarkable quantitative and qualitative differences between the two ethnobotanies. The gathering and use of some wild medicinal plants growing in meadows, woodlands, and higher mountain environments (Achillea, Centaurea, Dianthus, Ostrya, Picea, Polygonum, Potentilla, and Thymus) seems to have disappeared, whereas the collection of plants growing in more anthropogenic environments, or possibly promoted via contacts with the "reference" city of Genoa (the largest city close to Carrega and historically the economic and cultural centre to which the valley was mostly connected), has been introduced (i.e. ramsons, safflower, bitter oranges, black trumpets) or reinvigorated (rose petals). This trend corresponds to the remarkable changes in the local landscape ecology and agro-silvo-pastoral system that took place from the first half of the twentieth century, dramatically increasing woodland and secondary vegetation, and decreasing coppices, plantations, grasslands and segregating cultivated land. Conclusion The findings show a very difficult rearrangement of the LEK, as most of the areas the local actors still know are within their villages, and they no longer have daily experience in the rest of the abandoned woodland landscape (except for mushrooming and gathering chestnuts). This situation can be interpreted in two ways: as the start of the complete abandonment of the valley, or as a starting residual resilience lynchpin, which could possibly inspire new residents if the larger political-economic framework would promote measures for making the survival of the mountain settlements of this municipality possible, and not just a chimera.